Thong Thong Klek Art in Structural Functionalism Studies - Alvianto, Wibi Ardi; Florentinus, Totok Sumaryanto; Hartono, Hartono (Universitas Negeri Semarang, 2019)
Traditional Thong thong klek art is one of the traditional arts in Rembang regency. One team of Thong Thong Klek art is Gema Irama, which has an organizational structure that functions to regulate the organizational process of the team. Thong thong klek showis able torun well when all parts do their part well. The purpose of this study is to analyze and describe the structure of the organization and its function. Theoretically, this study uses a qualitative method with a monodisciplinary approach, namely sociology of art using structural functionalism theory. Data collection techniques were carried out by observation, interviews, and document studies. Checking the data validity were carried out by using source triangulation, followed by analyzing the data by reducing data, presenting data and drawing conclusions. The results of the study show that each part in the system of the arts organization can perform its functions properly and be mutually functional from one another. The Chairman has carried out his function well, but it turns out that there are also latent functions that are detrimental to the Gema Irama Thong Thong Klek Art. Other divisions encounter dysfunctions that hinder the development of the Gema Irama Thong Thong Klek art. Suggestions for Thong Thong Klek Gema Irama team is to be active in creating inovations according to the era development and always be consistent in prioritizing the values ​​of simplicity and kinship as the identity of the people of Rembang Regency.